Black seabream, spondyliosoma cantharus : stock structure in the eastern atlantic and characterisation of the biology and fishery in the portuguese coast - Neves, Ana (2019)
Tese de doutoramento, Ciências do Mar, Universidade de Lisboa, Faculdade de Ciências, 2018 In this thesis the stock structure of the black seabream, Spondyliosoma cantharus, along the Eastern Atlantic is explored using 4 different methodologies, body morphometry, otolith shape and stable isotopes ratio and genetics (mitochondrial and nuclear markers). Samples were gathered for five European areas (English Channel, Bay of Biscay, Galicia, west Portuguese coast – Peniche, and south Portuguese coast – Algarve), and two areas from African coast (Canary Islands and Angola). Results from morphometric analyses support the existence of different phenotypic stocks in each sampled area, while stable isotope ratios show fuzzier results with only 3 areas clearly distinguished: Angola, Canary Islands and Bay of Biscay. Genetic analyses were enhanced with samples from Mediterranean Sea and Cape Verde. A clear structuration is present between regions: North east Atlantic, Mediterranean Sea, Cape Verde and Angola, not being detected any population structuring within each region; however high levels of private haplotypes for all populations were observed, which can indicate that not enough dispersal/gene flow exists to homogenize more recent mutations at the ecological timescale. Integrating results from all methods, in a holistic stock structure analyses, the scenario with 6 different stock units in the North-eastern Atlantic is the most probable. Life history parameters for the species were also evaluated for the west Portuguese coast, since these are key parameters for a conscientious stock assessment. Maximum age of 17 years was assigned for a specimen with 38 cm. Age at growth was best described with the L00 hyperbolic modification of von Bertalanffy curve. Under this model, a change in growth occurs around 8 years, which corresponds roughly to the average age for sex reversal in the species. The estimated exploitation rate was relatively high (0.43 – 0.62), indicating that although the species is not the main target of ...